Market/place : exploring spaces of exchange - Berndt, Christian; Peck, Jamie; Rantisi, Norma M. (Norma Matuk) (Economic transformations (Newcastle upon Tyne, England), 2020)
Markets are seemingly omnipresent features of our economic landscape, and yet they do not exhibit a singular, essential or universal form. What are we to make of the fact that markets are never self-contained and selfregulating, but instead are tangled up and co-produced with all manner of governmental, social, and political processes? Furthermore, how are we to explain the persistent and often unruly "geographies" of markets, the causes and consequences of which remain elusive? From a variety of theoretical and disciplinary perspectives, this collection of original essays probes the question of how to think about markets spatially, and how to make sense of the geographies of marketization. In the process, Market/Place opens new frontiers for the emergent field of critical market studies, problematizing the "geography of markets" as an issue not only for self-identifying economic geographers, but as a demanding, interdisciplinary question